PROPOSAL OF RECONSTRUCTION OF POSTAL TRANSPORTATION NETWORK (Perner's Contacts, 2010)
The paper deals with the reconstruction of postal transportation network, specifically in Těšín and Třinec region. The reconstruction itself is a part of the centralization of delivery service which is to be implemented with using most modern technology and modern optimization methods. The existing postal network is not uniform and does not show elements of flexibility. The task of centralization of the delivery service is to find a balance in the system and create a network which will in effect form a flexible network, and of course will bring savings. The article describes the optimization methods that are suitable for creating a new and effective service system. Then these methods are applied to specific examples. It is important to note that proposal of reconstruction of postal transportation network concerns only service of packet segment.
Keywords: centralization; depot; delivery area; postal network